Amending certain provisions of the statute os rules enforcing the provisions of the import and export law and the system of exported and imported commodities examination and control procedures - Egypt : Ministry of Trade and Industry. The Egyptian Customs Authority (2025)
Ministry of trade and industry decree no. 818 of the year 2015 on amending certain provisions of the statute of rules Enforcing the Provisions of the import and export law and The System and imported commodities Examination and Control procedures – قرار وزير التجارة والصناعة رقم 818 لسنة 2015 بتعديل بعض أحكام القواعد المنفذة لأحكام قانون الاستيراد والتصدير ونظام إجراءات فحص ورقابة السلع المستوردة والمصدرة